2003
DOI: 10.1046/j.1468-2982.2003.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Behavioural Problems in Children and Adolescents with Primary Headache

Abstract: Psychiatric co-morbidity is an important risk factor for chronification of primary headache into adulthood. The aim of this study was to investigate the extent and clinical relevance of emotional and behavioural problems in children and adolescents with primary headache. Children and adolescents (n = 128) with primary headache (International Headache Society, codes 1.1, 1.2, 2.1) and 83 matched controls aged 6-18 years were examined by standardized dimensional psychometric tests (Child Behaviour Checklist, Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
89
1
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 51 publications
8
89
1
11
Order By: Relevance
“…Just et al (35) asserted that children and adolescents with primary headaches suffer more often from internalizing problems, depression, anxiety and somatization than do controls. They suggested that psychiatric comorbidity is an important risk factor for chronic primary headaches in adulthood.…”
Section: Fig 1 the Risk Analysis For Anxiety Or Depression Which Ismentioning
confidence: 99%
“…Just et al (35) asserted that children and adolescents with primary headaches suffer more often from internalizing problems, depression, anxiety and somatization than do controls. They suggested that psychiatric comorbidity is an important risk factor for chronic primary headaches in adulthood.…”
Section: Fig 1 the Risk Analysis For Anxiety Or Depression Which Ismentioning
confidence: 99%
“…22 Indeed, several mental health problems of this kind appear to commonly be present in migraine, including stress, anxiety, depression, somatization and panic disorder. [23][24][25][26] For example, a two-to six-fold increased risk for anxiety disorders has been shown for migraine, 27 and there is a high prevalence of major depression in migraine. 24,28,29 Stress plays the role of an important triggering factor for acute migraine attacks 29 and seems to regulate the maintenance of the disorder, the regularity of the attacks, 30 and the change from episodic to chronic state.…”
mentioning
confidence: 99%
“…[23][24][25][26] For example, a two-to six-fold increased risk for anxiety disorders has been shown for migraine, 27 and there is a high prevalence of major depression in migraine. 24,28,29 Stress plays the role of an important triggering factor for acute migraine attacks 29 and seems to regulate the maintenance of the disorder, the regularity of the attacks, 30 and the change from episodic to chronic state. 31 Although studies appear to be lacking in the literature, it is likely that the high stress level in migraine, if sustained, and with the additional impact of anxiety and depression, will result in burnout and a diagnosis of exhaustion syndrome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that over the years it has been increasingly studied, the relationship between headache and psychopathology remains poorly understood and it is still controversial [24] . Some literature fi ndings suggest the presence of specifi c personality traits [23] and psychiatric disorders (mainly anxiety and mood disorders) in headache sufferers [24][25][26] . However two thirds of headache children do not seem to present a clinically relevant psychopathology even if subclinical psychological disorders may occur [26] .…”
Section: Discussionmentioning
confidence: 99%